Effect of silane functionalized alumina on poly(vinyl butyral) nanocomposite films: Thermal, mechanical, and moisture barrier studies. Issue 7 (2nd December 2013) - Saravanan, S.; Gupta, Satyajit; Ramamurthy, Praveen C.; Madras, Giridhar
<x xml:space="preserve">Abstract</x> In this work, a hybrid‐polymer nanocomposite film, based on polyvinyl butyral/amino‐silane functionalized nano alumina, was fabricated by melt processing. The calcium degradation measurements suggest the functionalized nanocomposite films exhibit higher resistance towards moisture penetration as compared to the neat alumina loaded films. Thermal stability, mechanical strength, and contact angle studies of the composites were also conducted to evaluate the performance of the functionalized alumina loaded films. These nanocomposite films were encapsulated over Al/P3HT/ITO Schottky structured device. The changes observed in the current density of the devices to the applied voltage before and after accelerated aging conditions are presented. The nanocomposite with functionalized alumina films exhibits 50% change in current density, which is superior to that attained with neat and non‐functionalized films. POLYM. COMPOS., 35:1426–1435, 2014. © 2013 Society of Plastics Engineers